78th Annual Saskatchewan Christmas Bird Count - 2019 - Smith, Alan (Blue Jay, 2020)
The results of the 78th annual Saskatchewan Christmas Bird Count are in and, for the third time in the past four years, Gardiner Dam won the crown for most species observed at 45.